Implications of global warming for African climate - James, R; Rachel James (2014)
A 2°C increase in global mean temperature (ΔTg) has been widely adopted as a benchmark for dangerous climate change. However, there has been a lack of research into the implications of 2°C, or any other degree of warming, for Africa. In this thesis changes in African temperature and precipitation associated with 1°C, 2°C, 3°C, 4°C, and beyond are investigated for the first time, using output from 350 climate model experiments: a collection of simulations from international modelling centres (CMIP3), two Perturbed Physics Ensembles (PPEs), and a group of five regional models. The models project temperature and precipitation anomalies which increase in magnitude and spatial extent as global temperature rises, including a wet signal in East Africa, and drier conditions for African rainforests. The models consistently show that the evolution of change with global warming is gradual, even at 4°C and beyond; but the amplitude and direction of precipitation change at each ΔTg increment vary between models and between datasets. The PPEs project precipitation signals which are not represented by CMIP3, in particular a large drying (>0.5 mm day-1 °C-1) of western Africa. There are also important differences between global and regional models, especially in southern and West Africa (>1 mm day-1). Analysis of atmospheric circulation responses suggests that the higher resolution projections are no more credible in this case. Some of the variation between models can be understood as the result of untrustworthy simulations, leading to constraints on the PPEs, and casting doubt on the strong drying of west Sahel; but model evaluation is found to be limited by observations in the case of the Congo Basin. The implications of global warming are different depending on which models are consulted. The findings emphasise that caution should be exercised in the application of climate model data to inform mitigation debates.